2019
DOI: 10.1002/slct.201900709
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Hydrogenation of Tetralin to cis‐Decalin Using Ru Catalyst

Abstract: High activity Ru catalyst was prepared for the first time to produce cis‐decalin from tetralin hydrogenation. Supercritical CO2‐methanol method was used to prepare Ru supported catalyst. Using this catalyst, the yield of cis‐decalin could reach as high as 92.52%. Furthermore, the catalyst remained a high activity after five cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It was suggested that the competition for catalytic adsorption sites was responsible for inhibiting cis to trans isomerization up until significant tetralin conversion. Wang et al . synthesized a chromium-based metal organic framework (MOF) for use in tetralin hydrogenation reactions spanning 140–220 °C across a range of 30–70 bar H 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that the competition for catalytic adsorption sites was responsible for inhibiting cis to trans isomerization up until significant tetralin conversion. Wang et al . synthesized a chromium-based metal organic framework (MOF) for use in tetralin hydrogenation reactions spanning 140–220 °C across a range of 30–70 bar H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the competition for catalytic adsorption sites was responsible for inhibiting cis to trans isomerization up until significant tetralin conversion. Wang et al 16 synthesized a chromium-based metal organic framework (MOF) for use in tetralin hydrogenation reactions spanning 140−220 °C across a range of 30−70 bar H 2 . The results indicated that a highly enriched cis/trans ratio was achieved across all levels of tetralin conversion, due to a greater adsorption facility for tetralin by the highly porous MOF support.…”
Section: Introductionmentioning
confidence: 99%